2012
DOI: 10.1002/car.2204
|View full text |Cite
|
Sign up to set email alerts
|

Culpability Attributions towards Juvenile Female Prostitutes

Abstract: This study addresses a gap in the research literature concerning predictors of culpability attributions towards juvenile female prostitutes (JFPs). Three hundred undergraduate participants read a vignette describing a JFP and responded to a series of measures. Results supported a causal pathway whereby stronger perceiver sexism predicted stronger negative affective evaluations of, and weaker empathic reactions toward, the JFP. Stronger negative affective evaluations and weaker empathic reactions, in turn, pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
(60 reference statements)
4
29
0
Order By: Relevance
“…While seemingly counterintuitive, the significantly greater blame attributed to the DST victim indicates that respondents perceived her as a willing participant in prostitution, and it is possible for participants to have believed that she was in particular need of services for this very reason. This would align with prior research, where participants were less likely to recommend counseling for a prostituted youth when they found her culpable and believed she was unlikely to benefit (i.e., change) as a result of rehabilitative efforts (Menaker and Miller 2013). Another potential explanation is that, compared to the sexual assault and IPV scenarios, the DST vignette was distinct in depicting a more long-term and pervasive victimization.…”
Section: Ta Menaker and Ca Franklinsupporting
confidence: 63%
See 3 more Smart Citations
“…While seemingly counterintuitive, the significantly greater blame attributed to the DST victim indicates that respondents perceived her as a willing participant in prostitution, and it is possible for participants to have believed that she was in particular need of services for this very reason. This would align with prior research, where participants were less likely to recommend counseling for a prostituted youth when they found her culpable and believed she was unlikely to benefit (i.e., change) as a result of rehabilitative efforts (Menaker and Miller 2013). Another potential explanation is that, compared to the sexual assault and IPV scenarios, the DST vignette was distinct in depicting a more long-term and pervasive victimization.…”
Section: Ta Menaker and Ca Franklinsupporting
confidence: 63%
“…Moreover, perceptions of female victims of violence reflect cultural and societal attitudes about gender, gender relations, and sexuality. Research has examined victim blame toward rape survivors (e.g., Grubb and Harrower 2008;Whatley 1996), though there is comparatively less research on blame attributions toward IPV victims (e.g., Bryant and Spencer 2003;Flood and Pease 2009;Pavlou and Knowles 2001;Yamawaki et al 2012), and a conspicuous dearth of literature on DST (but see Franklin and Menaker 2014;Menaker and Franklin 2013a;Menaker and Miller 2013).…”
Section: Blame Toward Victims Of Gendered Violencementioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, victims were found less culpable for involvement in prostitution when observers read victimization history information (Menaker & Franklin, 2013;Menaker & Miller, 2013) and victimization history disclosure mattered similarly for White and African American prostituted youth (Menaker & Franklin, 2013). Research has also revealed that males tended to attribute more blame to victims as compared with females (Schneider, Mori, Lambert, & Wong, 2009;Workman & Freeburg, 1999).…”
Section: Perceptions Of Female Delinquentsmentioning
confidence: 99%